Cardiac autoimmunity in HIV related heart muscle disease. Issue 6 (1st June 1998) - Currie, P F; Goldman, J H; Caforio, A L P; Jacob, A J; Baig, M K; Brettle, R P; Haven, A J; Boon, N A; McKenna, W J
Abstract : Objective: To assess the frequency of circulating cardiac specific autoantibodies in HIV positive patients with and without echocardiographic evidence of left ventricular dysfunction. Subjects: 74 HIV positive patients including 28 with echocardiographic evidence of heart muscle disease, 52 HIV negative people at low risk of HIV infection, and 14 HIV negative drug users who had all undergone non-invasive cardiac assessment were studied along with a group of 200 healthy blood donors. Results: Cardiac autoantibodies detected by indirect immunofluorescence (serum dilution 1/10) were more common in the HIV positive patients (15%), particularly the HIV heart muscle disease group (21%), than in HIV negative controls (3.5%) (both p < 0.001). By elisa (dilution 1/320), abnormal anti-α myosin autoantibody concentrations were found more often in HIV patients with heart muscle disease (43%) than in HIV positive patients with normal hearts (19%) or in HIV negative controls (3%) (p < 0.05 and p < 0.001, respectively). Anti-α myosin autoantibody concentrations were greater in HIV positive patients than in HIV negative controls, regardless of cardiac status ((mean SD) 0.253 (0.155) v 0.170 (0.076); p = 0.003). In particular the mean antibody concentration was higher in the HIV heart muscle disease patients (0.291 (0.160) v 0.170 (0.076); p = 0.001) than in HIV negative controls. On follow up, six subjects with normal echocardiograms but raised autoantibody concentrations had died after a median of 298 days, three with left ventricular abnormalities at necropsy. This compared with a median survival of 536 days for 21 HIV positive patients with normal cardiological and immunological results. Conclusions: There is an increased frequency of circulating cardiac specific autoantibodies in HIV positive individuals, particularly those with heart muscle disease. The data support a role for cardiac autoimmunity in the pathogenesis of HIV related heart muscle disease, and suggest that cardiac autoantibodies may be markers of the development of left ventricular dysfunction in HIV positive patients with normal hearts.